MENINGKATKAN KEMAMPUAN MENGENAL ANGKA MELALUI BERMAIN PANCING ANGKA BAGI ANAK TUNAGRAHITA RINGAN - Afnita - Usti (Jurnal Penelitian Pendidikan Khusus, 2013)
The purpose of this research is to improve the ability to recognize numbers 1-10 mild mental retardation in children (RN and AD) in the Class D1 SLB Al-Ishlaah Padang. Type of research is a classroom action research (classroom action research) with two cycles performed in the form of collaboration with colleagues. The subjects in this study were classroom teachers and two classroom mild mental retardation D1 / C (RN and AD). Data obtained through observation and tests. Then analyzed qualitatively and quantitatively. The results showed that 1) the learning process in enhancing the ability to know the numbers 1-10 with through rod play figures with two cycles. Cycle I and Cycle II carried five (5) meetings. Each cycle begins with the planning, implementation (initial activity, core and end), observation, and analysis and reflection. 2) The results of the study proved that children's ability to recognize numbers up. This proved: before treatment (assessment) that the child's ability: RN scored (23.3), AD (20). I cycle an increase in the ability to say and show figures 1-10 RN values ​​obtained for (100) and AD (95). Cycle II the ability to know the numbers by writing the numbers 1-10 obtained values ​​for the RN as well (100) and AD (80). Thus, we can conclude that the playing rods can improve the ability to know the numbers numbers (say, show and write numbers 1-10) mild mental retardation children class D1 SLB Al-Ishlaah Padang.